Chelation-Assisted C–H and C–C Bond Activation of Allylic Alcohols by a Rh(I) Catalyst under Microwave Irradiation - Lee, Chang-Hee; Jun, Chul-Ho (Synlett, 2018)
Chelation-assisted Rh(I)-catalyzed ketone synthesis from allylic alcohols and alkenes through C–H and C–C bond activations under microwave irradiation was developed. Aldimine is formed via olefin isomerization of allyl alcohol under Rh(I) catalysis and condensation with 2-amino-3-picoline, followed by continuous C–H and C–C bond activations to produce a dialkyl ketone. The addition of piperidine accelerates the reaction rate by promoting aldimine formation under microwave conditions.
Keywords: rhodium; transition metals; hydroacylation; C–C bond activation; chelation assistance; microwave irradiation